A State-Of-The-Art Review on Structure-Soil-Structure Interaction (Sssi) and Site-City Interactions (Sci) - Saavedra-Flores, E (Elsevier Ltd, 2023)
Current seismic codes propose designing all new buildings in isolation from their neighbours. As a result, all modified seismic risks associated with interbuilding dynamic interactions through the soil are typically neglected. Recent population growth in cities (urbanization) and enhanced land costs have produced an increase in city building surface density, i.e., more closely spaced buildings. The difficulty of analysing groups of closely spaced buildings requires detailed geometric and material properties of both the existing and the new structures. Constructing new buildings adjacent to existing ones can increase or reduce the risk of existing structures. This potential risk to existing property owners represents a liability that is currently unquantified within the current seismic code framework. Thus, neglecting the increased seismic risk for some particular cases due to the coupling of adjacent buildings through the underlying soil is no longer reasonable. This phenomenon is referred to as Structure-Soil-Structure Interaction (SSSI) and can either magnify or attenuate the seismic response. The pages that follow provide a complete literature review of the leading developments of SSSI and Site-City Interaction effects (SCI). The pros and cons of the different methods are discussed, and it focuses on the theoretical idealization of SSSI by means of low-fidelity models with comparable predictive accuracy. The need for this reduced order modelling strategy to include more complex dynamic interactions among multiple building structures and soil at large length scales (i.e., city effects) is urgent and requires further investigation. Also, this paper will serve as standalone reference material for future research works and will pave the way for novel investigations in the context of SSI, SSSI and SCI, and their potential applications for developing next-generation seismic design codes and seismic risk assessments. Finally, recommendations for future research are proposed. © 2023 Institution of Structural Engineers